The molecular mechanism and utilization of ZmMs7-mediated dominant nuclear sterility in Oryza sativa L - Yusheng Xu; Yusheng Xu; Dingyang Yuan; Meijuan Duan (Frontiers in Plant Science)
IntroductionResearch on the molecular basis of dominant male sterility in rice and its application in sterile lines is significantly underdeveloped. This article aims to utilize dominant nuclear male sterile lines, which were created through the ectopic expression of ZmMs7 in the genetic background of rice, for the purpose of heterosis utilization.MethodsAt the same time, we conducted a study on the spatiotemporal expression characteristics of ZmMs7, performed transcriptome analysis, and implemented yeast two-hybrid experiments to elucidate its molecular regulatory mechanisms in mediating dominant nuclear male sterility in rice.ResultsThe results confirm the successful construction of a dominant nuclear male-sterile (NMS) vector system (p5126-ZmMs7-DsRed) using the exogenous male-sterile gene ZmMs7. This system comprises three modules: first, a dominant nuclear male-sterile (NMS) functional module driven by p5126, designed to achieve the dominant nuclear male-sterile trait; second, a fluorescence-based selection module driven by the endosperm-specific promoter LTP2, which facilitates the expression of the red fluorescent protein gene DsRed; and finally, a herbicide resistance screening module driven by the constitutive CaMV35S promoter, enabling the expression of the selectable marker Bar gene. The system has successfully developed a practical dominant male-sterile rice line characterized by complete pollen sterility, stable fertility, and straightforward visual seed selection, with no adverse effects on plant growth. In the hybrid offspring, approximately 50% of the seeds are genetically modified fluorescent seeds, while the remaining seeds are non-genetically modified and non-fluorescent. Transgenic plants Pro5126: GUS and ProZmMs7: GUS do not exhibit expression in roots, stems, leaves, or glumes. It is proposed that p5126 may enhance the expression of the ZmMs7 gene, which could lead to the up-regulation of the rice pollen fertility gene RIP1, as well as the down-regulation of OsMADS5 and the leafy glume sterile genes OsMADS1 and LHS1.DiscussionFurthermore, it was demonstrated that the proteins encoded by these three fertility genes interact with the protein encoded by ZmMs7. This study provides new insights into the molecular regulatory network governing male reproductive development in rice and offers a theoretical foundation and technical support for the development of novel male-sterile germplasm resources.